Pengembangan Kelompok Sadar Wisata (POKDARWIS) Kawasan Karst - Tohani, Entoh; Wibawa, Lutfi; Prasetyo, Iis (Universitas Negeri Yogyakarta, 2018)
The reported community development program aimed at increase the ability of tourism awareness group in managing the karts area tourism area; and build group awareness to exploit karst region tourism potential. This activity was held for 24 people involved in tourism awereness group namely the